ENT 530 Social Media Portfolio: Popia Ahh Mantap / Norman A/L Kam Ah Hwa - Kam Ah Hwa, Norman (2021)
POPIA AHH MANTAP is established to promote and sell variety of Popia that came freshly fromour recipe which main targeted is household and various type of people. Our POPIA AHH MANTAP are different from others as we serve unique recipe as our attentionis to introduce more variety of Popia to our generation. As we know, nowadays Popiaare not quite popular among teenagers but through unheralded user’s we believe POPIA AHH MANTAP will slowly and surely have its own potential to gain trust at marketshare and give savoury that will create long term bonding within family and friendsFurthermore, we are believed our POPIA AHH MANTAP can long lasted in market share due Malaysian popular recipe which is ‘kebab, bergedill ’ and others. Our delicious Popia willattract various type of people and tourists due to our simple handmade recipe and easyto prepare that will surely save time and energy. For instance, for workaholic peoplethey can save their time by eat our instant Popia there are easy to cook and provided indelicious flavor. We believe our POPIA AHH MANTAP can compete with others competitors because we haveour own credibility to produce our own Popia that will attract people by using our ownrecipe. Lastly, we always ensure that our Popia always in demand and are producedwith efficiently and effectively ways.